Odezwa [ulotka] . Appeal. Flier - Tymczasowa Komisja Koordynacyjna (TKK) NSZZ "Solidarność". (Tymczasowa Komisja Koordynacyjna (TKK) NSZZ "Solidarność", 1985)
Double-sided, b&w print on white paper. Flier contains a text of the appeal issued by the Interrim Coordination Comission of Solidarity on 16 July 1985 which calls for boycott of the October 1985 elections.